Importance of suicide prevention courses in health sciences and armed forces - Baños-Chaparro, Jonatan (2021)
Introduction: Suicide deaths reverberate families, unit members, and the military community. Recent studies point to the various risk factors and prevalence of suicidal behavior in members of the armed forces, as well as the lack of training in suicide prevention, evaluation, intervention, and postvention in health science curricula. Objective: describe the importance of including suicide prevention courses in health sciences and armed forces. Results: The relevance of education on suicidal behaviors, the main sections and contents in health sciences students, complementary training in students and members of the armed forces, and the benefits of training in suicide prevention are emphasized. In this sense, empirical evidence indicates that the inclusion of courses in the study plans or additional training for health professionals and members of the armed forces on suicide prevention are favorable for raising awareness, building and strengthening knowledge about suicide suicidal behaviors. Conclusions: There is interest and motivation to ensure that education is available to all, since adequate training allows a responsible, compassionate and evidence-based approach for the benefit of the community.